Pediatric living donor liver transplantation: A single center experiences - Ertuğrul, Gökhan; Hızarcı, Burcu (Journal of Surgery and Medicine, 2019)
Aim: The only definitive treatment of chronic liver disease (cholestatic, metabolic, autoimmune), acute liver failure and liver tumors are liver transplantation in pediatric patients. The aim of this study was to present the experience of our center on pediatric living donor liver transplantation and review of the literature. Methods: This is retrospective cohort study. Pediatric patients who receive living donor liver transplantation between December 2014 and December 2017 included in the study. Demographic features, complications after transplantation, and mortality rates were recorded. Results: A total 29 patients were included in the study. Mean age of cases were 3.1 (1-13) years, 18 (62.1%) of the patients were male. Mean Pediatric End-Stage Liver Disease (PELD) scores were 15.6 (-6-37). Mean follow-up period was 60 months. Complication was detected in 11 patients (37.9%) and 5 patients died (mortality rate: 17.9%). In our study, the causes of death were disseminated intravascular coagulation in three patients and sepsis due to biliary leakage in two patients. Conclusion: Complications and mortality rates related to pediatric patients with donor liver transplantation in our center are consistent with the literature.